Osteoporosis epidemiology update. - Cole, Z; Dennison, E; Cooper, C (2008)
Osteoporosis remains a major public health problem through its association with fragility fractures. Despite the availability of preventative therapeutic agents, the incidence and its associated costs continue to rise globally. Understanding osteoporosis epidemiology is essential to developing strategies to reduce the burden of osteoporotic fracture in the population. This article reviews the epidemiology of osteoporosis globally, highlighting recent advances. It describes the burden of common osteoporotic fractures, the associated morbidity and mortality, the clustering of fractures in individuals, and the identification of at-risk groups. It also highlights the development of new algorithms to identify individuals at high risk of fracture, enabling the implementation of appropriate treatment strategies.